2021
DOI: 10.1090/conm/768/15450
|View full text |Cite
|
Sign up to set email alerts
|

The Racah algebra: An overview and recent results

Abstract: Recent results on the Racah algebra Rn of rank n−2 are reviewed. Rn is defined in terms of generators and relations and sits in the centralizer of the diagonal action of su(1, 1) in U (su(1, 1)) ⊗n . Its connections with multivariate Racah polynomials are discussed. It is shown to be the symmetry algebra of the generic superintegrable model on the (n − 1) -sphere and a number of interesting realizations are provided.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…The vertices of this graph are given by the abelian subalgebras and the edges link two abelian algebras differing by only one generator. The web of the abelian subalgebras given in figure 1 generalizes the result of [9,10] where only the subalgebras of the type (C ij , C ijk ) have been considered. In this latter case, the connection graph reduces to a truncated tetrahedron.…”
Section: A Web Of Abelian Subalgebrasmentioning
confidence: 53%
See 2 more Smart Citations
“…The vertices of this graph are given by the abelian subalgebras and the edges link two abelian algebras differing by only one generator. The web of the abelian subalgebras given in figure 1 generalizes the result of [9,10] where only the subalgebras of the type (C ij , C ijk ) have been considered. In this latter case, the connection graph reduces to a truncated tetrahedron.…”
Section: A Web Of Abelian Subalgebrasmentioning
confidence: 53%
“…The above presentation of R( 4) is not unique and different other possibilities exist in the literature. Instead of C ij , another set of generators P ij = C ij − C i − C j (for i = j) and P ii = 2C i has been used previously to define the Racah algebra R(4) [9,10,5]. In this paper, we prefer to define the R(4) algebra using all the elements C I with I ⊆ {1, 2, 3, 4} since it simplifies the computations.…”
Section: Definitions and Casimir Elements Of The R(4) Algebramentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that quadratic algebras associated with n-dimensional systems are in general of higher rank [15,16,17,18]. These algebraic structures allow one to obtain useful information on quantum systems and their degenerate spectrum [19].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain these results we relied on the so-called left and right partial Casimir invariants, commonly encountered in the framework of coalgebra symmetry approach to superintegrability [33][34][35], that can be constructed from suitable linear combinations of the generalized Racah R(n) generators [36]. The generalized Racah algebra R(n) previously appeared as the symmetry algebra of the generic superintegrable model on the (n − 1)-sphere (see [22] and references therein) and pseudo-sphere [37]. It was proposed in [38] as a higher-rank generalisation of the rank one Racah algebra R(3), which is in turn the symmetry algebra of the generic superintegrable model on the 2-sphere [39,40].…”
Section: Introductionmentioning
confidence: 99%